Efficacy and safety of unilateral biportal endoscopy versus other spine surgery: A systematic review and meta-analysis - Zheng, Bin; Xu, Shuai; Guo, Chen; Jin, Linyu; Liu, Chenjun; Liu, Haiying (Frontiers in Surgery, 2022)
Abstract Background: To evaluate the efficacy and safety of Unilateral Biportal Endoscopy versus other spine surgery. Methods: Electronic databases systematically searched up to February 2022.Authors used Review Manager 5.3 to manage the data and carry out the review. Results: After the selection of 239 studies identified from electronic databases, 16 studies are eligible for inclusion criteria. 16 studies encompass total of 1488 patients: 653 patients in UBE group, 612 in MicroEndoscopic Discectomy group, 153 in Percutaneous Endoscopic Lumbar Discectomy group, 70 in Posterior Lumbar Interbody Fusion group. Unilateral Biportal Endoscopy is superior to MicroEndoscopic Discectomy in Visual Analogue Scale Back Pain 1-dayv(P<0.00001). There is no difference between Unilateral Biportal Endoscopy and MicroEndoscopic Discectomy in Visual Analogue Scale Leg Pain 1-day (P=0.25), long-term Visual Analogue Scale Back Pain (P=0.06), long-term Visual Analogue Scale Leg Pain (P=0.05), Oswestry Disability Index (P=0.09) and complications (P=0.19). Pooled analysis indicates Unilateral Biportal Endoscopy is similar with Percutaneous Endoscopic Lumbar Discectomy in Visual Analogue Scale Back Pain 1-day (P=0.71), Visual Analogue Scale Leg Pain 1-day (P=0.37), long-term Visual Analogue Scale Back Pain (P=0.75), long-term Visual Analogue Scale Leg Pain(P=0.41), Oswestry Disability Index (P=0.07) and complications (P=0.88). One study reports no difference between UBE and PLIF in long-term Visual Analogue Scale Back Pain, long-term Visual Analogue Scale Leg Pain and Oswestry Disability Index. Conclusions: Unilateral Biportal Endoscopy is superior to MicroEndoscopic Discectomy in instant back pain relief. Instant leg pain relief, future effects and safety are similar between Unilateral Biportal Endoscopy and MicroEndoscopic Discectomy. Unilateral Biportal Endoscopy and Percutaneous Endoscopic Lumbar Discectomy are similar in instant pain relief, future effects and safety. More evidence is needed to evaluate UBE versus Posterior Lumbar Interbody Fusion in efficacy and safety.